2016
DOI: 10.1111/1440-1681.12630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of JTV‐519 on stretch‐induced manifestations of mechanoelectric feedback

Abstract: JTV-519 is a 1,4-benzothiazepine derivative with multichannel effects that inhibits Ca release from the sarcoplasmic reticulum and stabilizes the closed state of the ryanodine receptor, preventing myocardial damage and the induction of arrhythmias during Ca overload. Mechanical stretch increases cellular Na inflow, activates the reverse mode of the Na /Ca exchanger, and modifies Ca handling and myocardial electrophysiology, favoring arrhythmogenesis. This study aims to determine whether JTV-519 modifies the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(165 reference statements)
1
1
0
Order By: Relevance
“…In the present work, as in previous studies on isolated Langendorff-perfused rabbit hearts [9], we found that stretch increased the AF dominant frequency, which can be considered as proarrhythmic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present work, as in previous studies on isolated Langendorff-perfused rabbit hearts [9], we found that stretch increased the AF dominant frequency, which can be considered as proarrhythmic.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, aside from Na v 1.5 and I NaL , ranolazine inhibits other ionic currents as I CaL and I Na-Ca , which are some of the mechanisms involved in the effects of stretch [6,9]. Nevertheless, the inhibition of these currents was weak at atrial level for the concentration used in this work [6].…”
Section: Discussionmentioning
confidence: 79%